Productive performance of soybean cultivars grown in southwest goiano (Research, Society and Development, 2022)
The development of the soybean crop is influenced by several environmental factors such as temperature, rainfall, relative air humidity, soil moisture and photoperiod. After sowing, the seeds are under pressure throughout the formation and maturation process in the field, which can influence the post-harvest quality. Based on the hypothesis that the behavior of soybean cultivars is expressed by the number of days it takes the plant to reach maturity, and this characteristic influences the plant's capacity for growth and grain production. The aim of this study was to evaluate the productivity of different commercial soybean cultivars from the late maturation group, recommended and cultivated in southwestern Goiás. The experimental design used was a randomized block, with 4 replications in a simple factorial scheme with 5 treatments: T1) SYN 13610; T2) SYN 15600; T3) M 6210; T4) M 7110; T5) ICS 7019. Biometric variables and soybean grain yield were measured. Data were subjected to analysis of variance (p